1995
DOI: 10.1002/em.2850250311
|View full text |Cite
|
Sign up to set email alerts
|

Statistical design and analysis of mutation studies in transgenic mice

Abstract: We have been working on identifying sources of variability in data from transgenic mouse mutation assays in order to develop appropriate statistical methods and designs for routine studies. Data from our lab and elsewhere point to the presence of significant animal-to-animal variability, which must be taken into account in statistical hypothesis tests. Here, the usual Cochran-Armitage (CA) test for trend in mutant frequencies, which takes the transgene as the experimental unit, and a generalized Cochran-Armita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…However, it is questionable whether sufficient data exist to adequately address the sources of variability issue in mutational spectra and its implication on the statistical evaluation. It is worth noting that methods described in Carr and Gorelick [1995], which are applicable to the overall mutant frequency data, can easily be extended to the category-specific MF data if animal variability were found to be important.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is questionable whether sufficient data exist to adequately address the sources of variability issue in mutational spectra and its implication on the statistical evaluation. It is worth noting that methods described in Carr and Gorelick [1995], which are applicable to the overall mutant frequency data, can easily be extended to the category-specific MF data if animal variability were found to be important.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were weighed weekly and the food consumed was measured twice weekly. Male and female rats were divided into eight groups, each consisting of 4 -6 rats, consistent with statistical recommendations by Carr and Gorelick [1995]. When the rats were 50 days old, 100 ppm PhIP (Ͼ98% HPLC pure, Toronto Research Chemicals, Toronto, Canada) were incorporated into the diet.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…Statistical analyses revealed that as few as 6-7 animals were required to detect a 50% induction above background (3 ϫ 10 Ϫ5 ), and 2-3 animals were required to detect a 100% induction (power ϭ 0.80, ␣ ϭ 0.05). A total of 5-10 animals͞treatment are recommended in transgenic rodent assays to give similar power of detection (16,17). To determine whether the cII gene in the fish was responsive to chemical mutagen exposure, we measured mutant frequencies in fish 15 days after exposure to 0, 60, or 120 mg͞liter ENU.…”
Section: ϫ5mentioning
confidence: 99%
“…To verify mutant cII phenotypes, plaques (30-100% total plaques) were cored, incubated in SM buffer (0.1 M NaCl͞0.01 M MgSO 4 ͞0.05 M Tris⅐HCl, pH 7.5͞0.01% gelatin) at room temperature for 1 h, and replated at low density under selective conditions. The minimum number of animals required to detect a significant induction of mutations was estimated by using a spontaneous mutant frequency of 3 ϫ 10 Ϫ5 , recovery of Ͼ300,000 pfu per animal, a power of 0.80, and ␣ ϭ 0.05 (16,17). Comparisons of mutation frequencies were tested for significance by using the generalized Cochran-Armitage test.…”
mentioning
confidence: 99%